A cross-sectional study on non-communicable morbidity among bank employees of Davangere City - Dhar, Ruchi; Kashyap, Ritu (International Journal Of Community Medicine And Public Health, 2021)
Background: Bank employees are an occupational group of people, experiencing both sedentary life-style and high level of stress in terms of handling financial aspects in their workplace. Thus, making bank employees vulnerable to develop non- communicable diseases. So far, very few studies have been done on bank employees to highlight the magnitude of Non-communicable morbidity and its risk factors. Hence, this study was undertaken to estimate the prevalence of non-communicable morbidity among the bank employees of Davangere city. Methods: A cross-sectional study was conducted among 390 bank employees of Davangere city. All the study subjects were selected by using probability proportionate to size technique. Data was collected by using pre-tested, semi-structure questionnaire. Height, weight, hip circumference, waist circumference and blood pressure were measured and recorded. Data was analyzed by using MS Excel and Open-Epi Info software version 2.2. Statistical test employed was chi-square and weightage of risk factors was calculated by mean. Results: The prevalence of hypertension, diabetes and obesity was 30.3%, 2.1% and 31.8% respectively. Conclusions: This study highlights the burden of non-communicable morbidity among bank employees.